Tabanidae (Diptera) of the American Museum of Natural History Collection - Henriques, Augusto Loureiro (Zootaxa, 2016)
A checklist of Tabanidae in the American Museum of Natural History was compiled. Over 9,000 specimens were studied. The currently accepted taxa names have been listed based on general catalogs and recent publications. Where possible, modern locality names are given and determiners of each species are provided. A total of 882 species are listed in alphabetical order; including 52 primary and 219 secondary types. The collection includes a substantial global representation of species records for this family.